Atmospheres in Urban Light - Shanti Sumartojo; Tim Edensor; Sarah Pink (Ambiances)
Inescapably spatial and located in experience, understanding atmospheres and their impact means close empirical attention to how they arise and are constituted, how they impress upon us, how they circulate and are shared, and what configures to make them feel differently for diverse people. In this article, we advance a dialogic autoethnographic methodology for attuning to, exploring and understanding atmospheres that accounts for them as they arise in the ongoing flow of experience of light. In this ethnographic approach, we research in atmospheres – that is, in the ongoing flow and change of shifting impressions and feelings constituted spatially by a multiplicity of elements. Taking a ‘light walk’ through inner city Melbourne as our example, we interrogate our experience of atmospheres in light, and also address how they might be purposefully constituted or designed.